The influence of cheerleading exercises on the schoolchildren's physical health of 5-9th forms - Bala T.M (Kharkov National Pedagogical University, 2012)
Physical health indexes of schoolchildren in 5-9th forms comprehensive secondary school are given in this article, and also their changes under the influence of specially matched cheerleading exercises. Schoolchildren's physical health level was determined by Robinson index, Skibinskiy index, Shapovalova index, Ketle index 2, Ruphie index. 255 schoolchildren aged 10-15 years took part in investigation, from which it was made five experimental groups and five control groups. Information of primary researches testify about the middle level of physical health of the children investigation contingent. It is set that inclusion cheerleading exercises in the process of experimental groups schoolchildren physical education, positively influenced on a level them physical health, which became above average level. Efficiency of cheerleading exercises influence is experimentally well-proven on schoolchildren Physical health in 5-9th forms.